Access Policy’s Over Encrypted Cloud Storage for Secure Deduplication - Kiran Kumar, G; Amarnath Reddy, E; Mamatha, B; Manisha, Kompally (International Journal of Engineering and Technology, 2018)
Attribute-Based Encryption (ABE) is a basic concept that considers public-key cryptography. Ciphertext-Policy ABE (CP-ABE) is one of the approaches used by ABE for data sharing in the cloud. In CP-ABE scheme, each user’s private key has a set of attributes and then the user decrypts a ciphertext if it holds a matching key. Our proposed system provides an extension to CP-ABE by implementing AES. AES uses a symmetric encryption key algorithm for a same set of keys. Our system provides a higher security through AES because of its complexity and helps in generating the content key . This key is used during the encryption of the original file over the cloud. Our methodology also focuses on deduplication to provide less consumption of cloud storage over the cloud. Another advantage of using this system is to provide an efficient way of data access via access policies for a certain set of credentials.